The potential of Citrullus colocynthis oil as a biocide against phytoparasitic nematodes. (October 2019) - Tarraf, Waed; Laquale, Sebastiano; De Mastro, Giuseppe; D'Addabbo, Trifone
Abstract: The high content of nematicidal fatty acids in Citrullus colocynthis seed oil could result in a novel product with a nematicidal potential. In this study, C. colocynthis oil was evaluated for its in vitro activity both against infective juveniles and eggs of the root-knot nematode Meloidogyne incognita and against infective specimens of the lesion nematode Pratylenchus vulnus, as well as against the suppressiveness of M. incognita in an experiment on potted tomatoes. The fatty acid composition of the tested oil was determined by gas chromatography analysis. Linoleic acid methyl ester (44.63%) and oleic acid (26.48%) were the two main fatty acid components, but there were also consistent percentages of erucic acid methyl ester (10.08%), palmitic acid (7.88%), and stearic acid (5.86%). C. colocynthis oil was highly toxic to M. incognita juveniles (>73% mortality) after a 24-h exposure to a 25 μg mL −1 solution, whereas infective specimens of P. vulnus were less sensitive with 46.6% mortality after a 24-h exposure to a 100 μg mL −1 oil solution. The viability of M. incognita eggs was strongly affected by C. colocynthis oil treatments with more than 64% egg mortality resulting from a 72-h immersion in a 250 μg mL −1 oil solution. Soil treatments with C. colocynthis oil resulted in a significant reduction of both M. incognit a eggs and gall formation on tomato roots, as well as of nematode density in the soil, in comparison to the non-treated control. Tomato plant growth was not negatively affected by C. colocynthis oil treatments, though a slight increase in plant biomass was recorded at just the highest concentrations of oil. This research demonstrates the nematicidal properties of C. colocynthis oil and, thus, its potential for the formulation of new products that could be applied in the context of organic or integrated management of phytoparasitic nematodes. Highlights: The nematicidal activity of Citrullus colocynthis seed oil has been evaluated. Seed oil contained fatty acids, mainly linoleic acid methyl ester and oleic acid. C. colocynthis oil showed a strong in vitro toxicity to phytoparasitic nematodes. Oil treatments were highly effective against root-knot nematode in the soil. Such oil could be a potential candidate for new formulation of nematicidal products.